Transgenic mice expressing a B cell growth and differentiation factor gene (interleukin 5) develop eosinophilia and autoantibody production (The Rockefeller University Press, 1991)
Interleukin 5 (IL-5) has been suggested to be involved in the growth and differentiation of B cells and eosinophils. Especially, Ly-1+ B cells, which have been considered to produce autoantibodies, are selectively developed by this lymphokine in long-term bone marrow culture. To envisage the possible engagement of IL-5 in the development of these cells in vivo, transgenic mice carrying the mouse IL-5 gene ligated with a metallothionein promoter were generated. Transgenic mice carrying the IL-5 gene exhibited elevated levels of IL-5 in the serum and an increase in the levels of serum IgM and IgA. A massive eosinophilia in peripheral blood, bone marrow, and spleen, and an infiltration of muscle and liver with eosinophils, were observed. When cadmium-containing saline was injected intraperitoneally into transgenic mice, IL-5 production was augmented about five times within 24 h, and a distinctive Ly-1+ B cell population became apparent in the spleen after 5 d. IL-5 receptors were detected on those cells by monoclonal antibodies against IL-5 receptors. Another interesting finding in these transgenic mice was an increase in polyreactive anti- DNA antibodies of IgM class. It is suggested, therefore, that aberrant expression of the IL-5 gene may induce accumulation of Ly-1+ B cells and eosinophils. Furthermore, this IL-5 transgenic mouse can be a model mouse for eosinophilia, and we can determine the role of IL-5 in the differentiation of Ly-1+ B cells and eosinophils by using this mouse.